Planting Shrubs in Florida Landscapes - Edward F. Gilman; Amy L. Shober; Kimberly A. Moore; Christine Wiese; Maria Kinslow Paz; S. Michele Scheiber (EDIS, 2009)
ENH-1129, a 4-page illustrated fact sheet by Edward F. Gilman, Amy L. Shober, Kimberly A. Moore, Christine Wiese, Maria Paz and S. Michele Scheiber, provides guidance for planting shrubs in Florida home landscapes. Includes additional resources. Published by the UF Department of Environmental Horticulture, June 2009.